2008
DOI: 10.1103/physrevb.78.075111
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structure factor of Luttinger liquids with quadratic energy dispersion and long-range interactions

Abstract: We calculate the dynamic structure factor S(ω, q) of spinless fermions in one dimension with quadratic energy dispersion k 2 /2m and long range density-density interaction whose Fourier transform fq is dominated by small momentum-transfers q q0 ≪ kF . Here q0 is a momentum-transfer cutoff and kF is the Fermi momentum. Using functional bosonization and the known properties of symmetrized closed fermion loops, we obtain an expansion of the inverse irreducible polarization to second order in the small parameter q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Evaluating the intergrals and extracting the leading divergence requires steps similar to the ones taken to compute the first order RPA-like diagram χ b 1 (q, ω) of Eq. (16). The leading behavior close to the lower threshold is…”
Section: Second Order Perturbation Theorymentioning
confidence: 94%
See 1 more Smart Citation
“…Evaluating the intergrals and extracting the leading divergence requires steps similar to the ones taken to compute the first order RPA-like diagram χ b 1 (q, ω) of Eq. (16). The leading behavior close to the lower threshold is…”
Section: Second Order Perturbation Theorymentioning
confidence: 94%
“…The idea is to include these perturbatively in the computation of observables and correlation functions [3]. However, the attempts in this direction led to divergences which indicate a breakdown of the corresponding perturbation theory [13][14][15][16]. The insights gained along this route are thus rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…For our model, the three-loops can be calculated analytically using the method outlined in the appendix of Ref. 48. Consider first the non-symmetrized three-loop defined in Eq.…”
Section: Appendix B: the Symmetrized Three-loopmentioning
confidence: 99%
“…In particular, the initial condition for the vertex with three external boson legs is For our model, the three-loops can be calculated analytically using the method outlined in the appendix of Ref. 48. Consider first the non-symmetrized three-loop defined in Eq.…”
Section: Appendix B: the Symmetrized Three-loopmentioning
confidence: 99%
“…and its modifications have been investigated actively [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. These studies have demonstrated that combined effect of the marginal and the irrelevant operators has important and measurable consequences for system's properties.…”
mentioning
confidence: 99%